THE IMPACT OF FIRM QUANTITATIVE PROFITABILITY ON LIQUIDITY AND SOLVENCY ON AUDITORS' PERCEPTIONS OF ORGANIZATIONAL CHANGE (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The continuity of the company's operations, in addition to risks arising from various internal and external sources, is the hope of every organization in its efforts to achieve company goals. The purpose of this study was to determine the effect of company size, profitability, liquidity and financing on perceptions of the sustainability of companies engaged in the transportation sector listed on the Indonesia Stock Exchange for the 2018-2021 period. The second data used is from the Indonesia Stock Exchange, and the data source is www.idx.co.id. In this study, the sample was selected according to the purpose of sampling and 16 companies were selected as the sample. Data analysis using multiple linear regression analysis. The results of the study show that company size, profitability, liquidity and financing have an effect on business continuity .